2015
DOI: 10.1007/s00401-015-1445-9
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automated quantification of C9orf72 expansion size reveals inverse correlation between hexanucleotide repeat number and disease duration in frontotemporal degeneration

Abstract: We investigated whether chromosome 9 open reading frame 72 hexanucleotide repeat expansion (C9orf72 expansion) size in peripheral DNA was associated with clinical differences in frontotemporal degeneration (FTD) and amyotrophic lateral sclerosis (ALS) linked to C9orf72 repeat expansion mutations. A novel quantification workflow was developed to measure C9orf72 expansion size by Southern blot densitometry in a cross-sectional cohort of C9orf72 expansion carriers with FTD (n= 39), ALS (n= 33), both (n=35), or wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 43 publications
4
65
1
Order By: Relevance
“…Similar to what was observed in other repeat expansion diseases, the repeat size was also found to be associated with sample collection time [22, 23]. C9orf72 repeat expansion sizes have been widely reported to vary in different tissue types and cell types [19, 2224], indicating the expansion of repeats might be caused by some cell division-independent mechanism in addition to somatic instability.…”
Section: Discovery Of Ggggcc/ccccgg Hexanucleotide Repeat Expansiosupporting
confidence: 75%
See 2 more Smart Citations
“…Similar to what was observed in other repeat expansion diseases, the repeat size was also found to be associated with sample collection time [22, 23]. C9orf72 repeat expansion sizes have been widely reported to vary in different tissue types and cell types [19, 2224], indicating the expansion of repeats might be caused by some cell division-independent mechanism in addition to somatic instability.…”
Section: Discovery Of Ggggcc/ccccgg Hexanucleotide Repeat Expansiosupporting
confidence: 75%
“…However, variable ranges of repeat number have been reported for controls and patients: fewer than 14 repeats in controls as 20–22 repeats were associated with FTD [20]; fewer than 23 repeats in controls [15]; 800–4400 repeats in patients [19]; 0–30 repeats in controls and more than 500 repeats in patients [21]. And finally a more recent study employing a southern blot based semi-automated quantification showed that most control carry fewer than 10 repeats, while patients carry 300–3800 repeats [22]. …”
Section: Discovery Of Ggggcc/ccccgg Hexanucleotide Repeat Expansiomentioning
confidence: 99%
See 1 more Smart Citation
“…Working in parallel, Brian Traynor and colleagues independently discovered pathogenic GGGGCC repeat expansion in C9ORF72 79 . Similar to numerous other neurodegenerative diseases caused by microsatellite expansion, there appears to be an inverse relationship between repeat expansion length and disease severity 102,103 . Affected individuals apparently inherit hundreds of repeat copies, but these undergo expansion to 3000–5000 copies in cells of the nervous system 104 .…”
Section: The Curious Case Of C9orf72-related Als/ftdmentioning
confidence: 68%
“…Alignment of sequence reads and variant calling were assessed by SureCall software (Agilent). In addition, cases were tested for the C9orf72 hexanucleotide repeat expansion as previously described [32]. …”
Section: Methodsmentioning
confidence: 99%